Left ventricular hypertrophy in hypertension: Correlation between electrocardiography and echocardiography - Prakash, O; Karki, P; Sharma, SK (Kathmandu University Medical Journal, 2010)
Background: Hypertension is an important modifiable cardiovascular risk factor. Left ventricular hypertrophy - the marker of hypertension, has emerged as an independent risk factor that can be detected by electrocardiography (ECG) and echocardiography (ECHO). Objective: Correlation of electrocardiography and echocardiographically detected left ventricular hypertrophy in hypertensive patients. Materials and methods: Hundred patients with hypertension were studied for left ventricular hypertrophy by the help of electrocardiography and echocardiography. Left ventricular hypertrophy on ECG was assessed by the help of Sokolow- Lyon Voltage Criteria (SLV) and Romhilt - Estes Point Score (R/E). Results: Among 100 patients, 60 were males and 40 were females. Mean age for male was 54.82 ± 12.10 years and 52.95 ± 11.63 years for female. The mean systolic blood pressure for male was 150.47 ± 20 mmHg and for female 148.60 ± 16.95 mmHg; where as Diastolic blood pressure for male was 93.67 ± 11.13 mmHg and for female it was 96.05 ± 12.47 mmHg. Echocardiography detected left ventricular hypertrophy in 64% patients. Electrocardiography detected Left Ventricular Hypertrophy by R/E and SLV criteria 13% and 34% respectively. Conclusion: In developing and under developed country ECG is a useful tool for detection of LVH where the facilities of echocardiography and trained echocardiographer are still not in a common man's reach. Key words: Left ventricular hypertrophy; Hypertension DOI: 10.3126/kumj.v7i2.2698 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 97-103